Asymmetric Barrier Lyapunov Function-Based Wheel Slip Control for Antilock Braking System - Xiaolei Chen; Zhiyong Dai; Hui Lin; Yanan Qiu; Xiaogeng Liang (International Journal of Aerospace Engineering)
As an important device of the aircraft landing system, the antilock braking system (ABS) has a function to avoid aircraft wheels self-locking. To deal with the strong nonlinear characteristics, complex nonlinear control schemes are applied in ABS. However, none of existing control schemes focus on the braking operating status, which directly reflects wheels self-locking degree. In this paper, the braking operating status region is divided into three regions: the healthy region, the light slip region, and the deep slip region. An ABLF-based wheel slip controller is proposed for ABS to constrain the braking system operating status in the healthy region and the light slip region. Therefore the ABS will be prevented from operating in the deep slip region. Under the proposed control scheme, self-locking is avoided completely and zero steady state error tracking of the wheel optimal slip ratio is implemented. The Hardware-In-Loop (HIL) experiments have validated the effectiveness of the proposed controller.